Preparation of a CeO2–ZrO2 based nano-composite with enhanced thermal stability by a novel chelating precipitation method. Issue 23 (1st December 2021) - Wang, Qi; Du, Fu; Hou, Yongke; Zhang, Yongqi; Cui, Meisheng; Zhang, Yihe
Abstract: In this study, a chelating agent is introduced to prepare CeO2 –ZrO2 nano-composite through a precipitation process. The physicochemical properties of the oxide precursors, nano composite materials are strongly dependent on the preparation method and whether a chelating agent is used. Adding an appropriate quantity of chelating agent SO4 2− can facilitate thermal stability and phase structure uniformity of CeO2 –ZrO2 mixed oxides. The calculation results showed that the Gibbs free energy of chelating complex of [ZrSO4 ] 2+ (ΔG = −127.2469 kJ/mol) is higher than the [Ce(III)SO4 ] + (ΔG = -29.8279 kJ/mol). The precipitation chemical potential of Zr 4+ moves close to the precipitation chemical potential of Ce 3+ . The novel and low-cost chelating precipitation method can modify the homogeneity of the compounds at the atomic scale, which can offer a powerful opportunity for, and provide direction in, the design of materials with exceptional properties.